Fluid pathways and high‐P metasomatism in a subducted continental slice (Mt. Emilius klippe, W. Alps). (16th January 2017) - Angiboust, S.; Yamato, P.; Hertgen, S.; Hyppolito, T.; Bebout, G. E.; Morales, L.
Abstract: The Mt. Emilius klippe (Western Alps, Italy) corresponds to a segment of the stretched Adriatic continental margin metamorphosed at granulite facies during Permian. This slice was subducted during the early Cenozoic Alpine subduction with the underlying eclogite facies remnants of the Tethyan seafloor (Zermatt‐Saas zone). Near the base of the Mt. Emilius massif, there is a shear zone with eclogite facies hydrofracture systems associated with deformation‐induced re‐equilibration of granulites during high‐ P metamorphism. In the basal part of the massif, a pluri‐hectometre domain of sheared mafic boudins is hosted in the granulitic paragneiss. In these mafic boudins, there are garnetites, garnet veins and clinopyroxenites, as well as clinozoisite and calcite veins. These features record multiple events of fracture opening, brecciation, boudinage and parallelization of structures coevally with fluid–rock interaction, metasomatism and volume change. This integrated petrological, micro‐textural and geochemical investigation illustrates the multiplicity and the chemical variability of fluid sources during prograde to peak metamorphic evolution in the lawsonite–eclogite‐facies field (at ~2.15–2.4 GPa, 500–550 °C) during subduction of the Mt. Emilius slice. The calcite veins crosscutting the garnetites have relatively low δ 18 OVSMOW values ( ∼ +6.5‰) near those for marble layers (and nearby calcsilicates) embedded within the metasomatized granulites (+8 to +10‰). It is proposed that infiltration of externally‐derived H2 O‐rich fluids derived from the plate interface flushed the marbles, promoting decarbonation followed by short‐distance transport and re‐precipitation along garnetite fractures. This study highlights the importance of inherited structural heterogeneities (such as mafic bodies or sills) in localizing deformation, draining fluids from the downgoing plate and creating long‐lasting mechanical instabilities during subduction zone deformation.